Diagnosticar como os estudantes do primeiro segmento do ensino fundamental resolvem problemas matemáticos envolvendo o tratamento da informação - Lima, Anna Fabrícia Carvalho de (2013)
The present study aimed to investigate how the students in the 5th grade of elementary school of public schools Mamanguape, Paraíba, resolve issues involving the block contents on data processing. As a basis for the study adopted as the main theoretical Lopes (1998), Santos (2009), among other authors, and official documents: Brazil (1997) and Paraíba (2010), as well as national programs evaluation, IDEB, presenting their latest results and Descriptors Elementary School to serve as evaluators of the skills and competencies of students in elementary school internal transition from 5th to 6th grade. The survey was administered to 136 students from five classes of 5th year distributed in three public schools Mamanguape, Paraíba. The methodology used to validate the theoretical approach was descriptive and exploratory study, according to the research objectives, designed based on materials published on the subject. As to typicality study characterized by a simple case study with respect to data analysis. To adopt this as the primary research instrument, a semi-structured questionnaire applied with students. The study was conducted from April to May 2013. As a result it has to be the main conceptions of students about the issue involving the treatment of information in solving mathematical problems was unsatisfactory when compared with the indexes of mathematical descriptors for the year investigated. We realize that many students had difficulties in most matters involving the theme. The study indicates that we need more effective public policies regarding the teaching and learning of the children in our county.